Professional conduct during breast and uterine/cervical cancer screening consultations - Fernanda Martins Bertocchi; Betânia Maria Fernandes; Maria Inês Gomes de Almeida; Sandra Carvalho de Freitas; Carla Cardi Nepomuceno de Paiva; Elaine Amaral de Paula (Rev Rene)
Aimed to evaluate the behavior of professionals regarding checking medical history (anamneses) and the physical examination performed in screening consultation for breast and cervical cancer in primary health care. This is a descriptive cross-sectional study of quantitative analysis, and was conducted in Minas Gerais, MG, Brazil.  For evaluation purposes, a structured questionnaire was answered by women who attended a consultation with nurses or doctors, from December 2012 to January 2013. The research instrument contained sociodemographic questions and questions related to medical history (anamneses), physical and gynecological examination, as recommended by the Ministry of Health. Fifty women were interviewed, averaging 40 years of age. The results showed incomplete anamnesis, physical and gynecological examination in all consultations. For full promotion of women’s health attention, it is necessary to comply with Ministry of Health recommendations.